Studi Pengaruh Rekonfigurasi Loop Scheme Terhadap Keandalan Penyulang Blahkiuh dan Penyulang Panglan - yoga, bagus widyananda; Arjana, I Gede Dyana; Pemayun, A.A Gede Maharta (Majalah Ilmiah Teknologi Elektro; Vol 17 No 1 (2018): (Januari - April) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2018.v17i01.P05, 2017)
Abstract —To improve reliability, the do loop system reconfiguration scheme to Blahkiuh feeders and feeders Panglan, by analyzing the calculation SAIFI and SAIDI, can the economy in terms of pressing / kWh minimize the number of unsold losses.   Analysis of calculation results Blahkiuh feeders and feeder reconfiguration Panglan before result Blahkiuh feeder SAIFI 16.534   times/customers/year and the results SAIDI 35.894 hours/customer/year so the numbers of unsold kWh losses from the calculation not save 227,640.841 kWh energy equivalent to Rp 318,718,182.6, while for the results obtained Panglan feeder SAIFI 23.59   times/customer/year, the results of SAIDI 87.39 hours/   customer/year and the calculation results energy not save 238,037.099   kWh equivalent to Rp 364,672,835.7.   After reconfiguration can minimize the number of SAIFI / SAIDI and losses, the results obtained Blahkiuh feeder SAIFI 2,089 times/   customers/year and the results SAIDI of 4.27 hours/customer/year, results energy not save 13369.314 kWh equivalent to Rp 20,481,733.86. For Panglan feeder SAIFI results obtained 1,218 times/customers/year and the results SAIDI 1,242 hours/   customer/year, results energy not save 3880.571 kWh equivalent to Rp 5,945,033.22.   I ntisari — Untuk meningkatkan keandalan maka dilakukan rekonfigurasi sistem  loop scheme  pada penyulang Blahkiuh dan penyulang Panglan, dengan menganalisa perhitungan  SAIFI  dan  SAIDI , ditinjau dari segi ekonomi mampukah menekan/   memperkecil angka kerugian  kWh  yang tidak terjual.   Hasil Analisa perhitungan penyulang Blahkiuh dan penyulang Panglan sebelum rekonfigurasi diperoleh hasil  SAIFI  penyulang Blahkiuh 16,534 kali/pelanggan/tahun dan hasil  SAIDI  35,894 jam/pelanggan/tahun sehingga angka kerugian  kWh  tidak terjual dari hasil perhitungan  energy not save  227.640,841  kWh  setara dengan Rp 318.718.182,6, sedangkan untuk penyulang Panglan diperoleh hasil  SAIFI  23,59 kali/pelanggan/tahun, hasil  SAIDI  87,39 jam/pelanggan/tahun dan hasil perhitungan  energy not save  238.037,099  kWh  setara dengan Rp 364.672.835,7.   Setelah rekonfigurasi dapat memperkecil angka  SAIFI/SAIDI  dan kerugian yang dialami, pada penyulang Blahkiuh didapat hasil  SAIFI  2,089 kali/pelanggan/tahun dan hasil  SAIDI  4,27 jam/pelanggan/tahun, hasil  energy not save  13.369,314  kWh  setara dengan Rp 20.481.733,86. Untuk penyulang Panglan didapat hasil  SAIFI  1,218 kali/pelanggan/tahun dan hasil  SAIDI  1,242 jam/pelanggan/tahun, hasil  energy not save  3.880,571  kWh  setara dengan Rp 5.945.033,22.   Kata Kunci : Sistem  radial ,  Loop scheme ,  SAIFI/SAIDI ,  Energy   not  save [Turnitin Chek 12% 13042017]